The Influence of Forests on Freshwater Fish in the Tropics: A Systematic Review. (1st April 2020) - Lo, Michaela; Reed, James; Castello, Leandro; Steel, E Ashley; Frimpong, Emmanuel A; Ickowitz, Amy
Abstract: Tropical forests influence freshwater fish through multiple pathways, only some of which are well documented. We systematically reviewed the literature to assess the current state of knowledge on forests and freshwater fish in the tropics. The existing evidence is mostly concentrated in the neotropics. The majority of studies provided evidence that fish diversity was higher where there was more forest cover; this was related to the greater heterogeneity of resources in forested environments that could support a wider range of species. Studies quantifying fish abundance (or biomass) showed mixed relationships with forest cover, depending on species-specific habitat preferences. We identify the key challenges limiting our current understanding of the forest–fish nexus and provide recommendations for future research to address these knowledge gaps. A clear understanding of the functional pathways in forest–freshwater ecosystems can improve evidence-based policy development concerned with deforestation, biodiversity conservation, and food insecurity in the tropics.